Neuroprognostication of Cardiac Arrest Patients: Outcomes of Importance - Cronberg, Tobias (Seminars in Respiratory and Critical Care Medicine, 2017)
During the last two decades, survival rates after cardiac arrest have increased while the fraction of patients surviving with a severe neurological disability or vegetative state has decreased in many countries. While improved survival is due to improvements in the whole “chain of survival,” improved methods for prognostication of neurological outcome may be of major importance for the lower disability rates. Patients who are resuscitated and treated in intensive care will die mainly from the withdrawal of life-sustaining (WLST) therapy due to presumed poor chances of meaningful neurological recovery. To ensure high-quality decision-making and to reduce the risk of premature withdrawal of care, implementation of local protocols is crucial and should be guided by international recommendations. Despite rigorous neurological prognostication, cognitive impairment and related psychological distress and reduced participation in society will still be relevant concerns for cardiac arrest survivors. The commonly used outcome measures are not designed to provide information on these domains. Follow-up of the cardiac arrest survivor needs to consider the cardiovascular burden as an important factor to prevent cognitive difficulties and future decline.
Keywords: cardiac arrest; coma; prognosis; outcome